MODERN TECHNOLOGICAL SOLUTIONS IN THE TREATMENT OF OBSTRUCTIVE SLEEP APNEA: A REVIEW OF INNOVATIONS AND THEIR SOCIAL IMPACT - Mateusz Stronczyński; Dawid Głaz; Szymon Zysiak; Maksymilian Głaz; Natalia Kamińska; Jędrzej Zaguła; Magdalena Stolarczyk; Wojciech Sołtys; Aleksandra Jagura-Sukiennik; Łukasz Deska (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: The aim of this review is to analyze technological advancements in the treatment of Obstructive Sleep Apnea (OSA) published between 2019 and 2025, with a specific focus on their impact on therapeutic adherence and public health. Materials and methods: A comprehensive literature review was conducted utilizing key databases such as PubMed, Scopus, Web of Science, and Google Scholar. The selection process prioritized innovative technological solutions, telemedicine applications, and e-health concepts. Results: The comprehensive review of the scientific literature revealed several technological advancements significantly impacting the treatment of Obstructive Sleep Apnea: • Hypoglossal Nerve Stimulation: HNS serves as an effective alternative for moderate to severe OSA patients intolerant to CPAP [1]. This implantable treatment stimulates the hypoglossal nerve, activating muscles to maintain upper airway patency during sleep, resulting in significant reductions in Apnea-Hypopnea Index and improved sleep quality [2,3]. • Advanced Algorithms in PAP Devices: Integrating AI and machine learning into PAP devices optimizes treatment and boosts patient adherence [4]. These algorithms analyze CPAP data to predict adherence issues, enabling clinicians to tailor interventions and personalize strategies for better patient outcomes [5]. • Telemedicine: Telemedicine has advanced OSA management through remote patient interaction, monitoring, and follow-up [6]. This remote care often leads to comparable or improved treatment compliance, offering cost-effective solutions and increasing access to specialized care [7]. • 3D Printing in Oral Appliances: 3D printing revolutionizes the fabrication of custom Mandibular Advancement Devices for OSA [8,9]. Utilizing digital workflows from intraoral scanning to CAD design, highly precise appliances are produced, improving patient comfort and adherence [9]. Conclusion: The introduction of new technologies in OSA treatment, such as hypoglossal nerve stimulation, improved algorithms in PAP devices, telemedicine, and 3D printing, holds significant potential for increasing patient therapeutic adherence [10]. These technologies favor therapy personalization, which is crucial given the diverse pathophysiology and phenotypes of OSA [2]. Improved compliance and the availability of personalized treatment methods directly translate into better public health outcomes, a reduction in the risk of cardiovascular and metabolic complications, and an overall improvement in the quality of life for OSA patients [11, 12]. However, attention must be paid to ensuring that the implementation of these innovations is conducted thoughtfully, so as not to exacerbate existing inequalities in access to healthcare [12].